Enhancement of phase-change evaporators with zeotropic refrigerant mixture using metal foams. (March 2017) - Bamorovat Abadi, Gholamreza; Kim, Kyung Chun
Highlights: Zeotropic mixture in a metal foam heat exchanger has been studied experimentally. R245fa and mixture of R245fa/R134a (0.6/0.4) were investigated. Heat transfer enhancement was observed for both types of refrigerants. 20 PPI metal foam proved to have the best performance in all cases. New correlations were proposed for two-phase flow parameters. Abstract: Almost all thermal systems use some kind of heat exchanger. In many cases, evaporators are needed for systems such as organic Rankine cycle (ORC) systems. Evaporators contribute to a big portion of the capital cost, and their price is directly related to their size or transfer area. Highly porous open-cell metal foams are being considered to improve performance while keeping the size of heat exchangers small. This study experimentally investigates the degradation of the heat transfer coefficient of zeotropic mixtures during phase change in a plate heat exchanger with metal-foam-filled channels. The working fluids were pure R245fa and a zeotropic mixture of R245fa/R134a (0.6/0.4 molar ratio). The results show that the metal foams significantly increase the recovered heat, overall heat transfer coefficient, and effectiveness of the heat exchanger for mass flux ranging from 90 to 290 kg/m 2 s, but at the expense of increasing the pressure drop. The same improvement was observed for the mixture of refrigerants. The degraded heat transfer coefficient of the mixture compared to the pure refrigerants was recovered by the introduction of metal foams to the system. New correlations are proposed to predict the two-phase heat transfer coefficient of both pure R245fa and the refrigerant mixture in metal foam evaporators.